Career choices of the first seven cohorts of JCU MBBS graduates: producing generalists for regional, rural and remote northern Australia - Torres Woolley; Sarah Larkins; Tarun Sen Gupta (Rural and Remote Health, 2024)
Introduction: Generalism in the health workforce has been established as an important strategy to address health workforce maldistribution. Thus, to best serve the medical needs of northern Australia, the James Cook University (JCU) College of Medicine and Dentistry has a mission to produce graduates who both practise in the region and have a generalist orientation. This study investigated the postgraduate qualifications and key factors that shaped the current career choice of JCU medical graduates, and whether JCU graduates are more likely to choose generalist careers than other Australian medical practitioners of a similar level of experience. Methods: JCU medical graduate data were obtained via cross-sectional survey of 298 early career JCU medical graduates from postgraduate year (PGY) 4 to PGY 10 (the first seven cohorts) who had consented to be contacted for further studies and were still contactable (n=180, response rate=60%). Australian medical graduate data were obtained via the National Health Workforce Dataset released by the Department of Health. Results: Compared to a group of Australian medical graduates with similar years of experience, JCU medical graduates are significantly more likely to choose careers as ‘generalists’ (general practitioners/rural generalists (p=0.044)) or ‘generalist specialists’ in general surgery (p=0.008), general paediatrics (p=0.008), obstetrics and gynaecology (p=0.038) and emergency medicine (borderline significance p=0.058). However, they are less likely to be ‘specialist specialists’ such as pathologists/radiologists (p=0.003) or a physician subspecialty (p=0.004). Key factors identified as influencing current career choice included ‘interest developed or strengthened during undergraduate training’, ‘interest developed from early postgraduate career experiences’, ‘specialty has a good work–life balance’, ‘specialty involves continuity of care with patients’, ‘interest in rural practice’, ‘enjoy a wide scope of practice/being a generalist’ and ‘mentors’. Conclusions: The JCU medical school produces significantly more graduates with a generalist rather than specialist career focus compared to a similarly experienced group of Australian medical practitioners. Contributing factors may include the JCU selection process, and the curricular focus on providing students with a wide range of generalist experiences and exposure to rural, remote, Indigenous and tropical health. Developing approaches that facilitate local vocational training and subsequent specialist practice is also an important part of the regional, rural and remote training pathway. Lastly, the findings suggest JCU medical graduates choose a career that is not only compatible with regional, rural or remote practice, but also involves continuity of care with patients, a wide scope of practice and a good work–life balance, and that this choice has been influenced by a combination of undergraduate and early career experiences. These findings are in line with international evidence and have implications for other jurisdictions planning an educational and workforce strategy to meet the needs of their own regional, rural and remote locations.